International Lending Patterns of U.S. Commercial Banks - Jain, Arvind K. (Journal of International Business Studies, 1986)
The international lending behavior of the U.S. commercial banks depends upon economic links between countries. Much of the difference between the international loan portfolios of U.S. banks and those of the non-U.S. banks may be explained by the patterns of trade flows and investments by nonfinancial corporations. These trade flows and investment patterns explain most of the variations in the bank lending patterns for 70-80 percent of the countries. The analysis points to an increasing influence of economic ties on the lending process over time.